2017
DOI: 10.1002/ijgo.12258
|View full text |Cite
|
Sign up to set email alerts
|

Unmet contraceptive needs in rural communities in the Dominican Republic during an international Zika virus outbreak

Abstract: K E Y W O R D S : Contraception; Dominican Republic; Family planning; Long-acting reversible contraception; Zika virusZika virus infection during pregnancy is linked with adverse pregnancy and birth outcomes. 1,2 Therefore, women and their partners need education about the complications of Zika virus and reliable contraception in the context of this global health concern. Studies confirm the superiority of long-acting reversible contraceptives, which are desirable during Zika virus outbreaks to prevent uninten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Additionally, our findings show that only one person (2.9%) in our sample used condoms to prevent the spread of Zika. In a separate study conducted in rural Dominican communities, 93% of women were found to be aware of Zika but this awareness did not impact their contraceptive usage [47]. These differences indicate that there is notable variation in Zika knowledge across Dominican communities which may be a result of inaccessibility of medical services and products, such as contraceptives [47].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our findings show that only one person (2.9%) in our sample used condoms to prevent the spread of Zika. In a separate study conducted in rural Dominican communities, 93% of women were found to be aware of Zika but this awareness did not impact their contraceptive usage [47]. These differences indicate that there is notable variation in Zika knowledge across Dominican communities which may be a result of inaccessibility of medical services and products, such as contraceptives [47].…”
Section: Discussionmentioning
confidence: 99%
“…To achieve research aims, a multi‐site, mixed‐methods, cross‐sectional study was conducted in which patients from four villages, known as bateyes, were surveyed immediately following their visit to the clinic. Methods employed were tested in a 2016 proof of concept study . The DMU and Timmy Global Health institutional review boards approved both the 2016 proof of concept study and 2017 pilot study.…”
Section: Methodsmentioning
confidence: 99%
“…Methods employed were tested in a 2016 proof of concept study. 7 The DMU and Timmy Global Health institutional review boards approved both the 2016 proof of concept study and 2017 pilot study.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, broader strategies should explore and be sensitive to these complexities in the context of Zika. Activities like provider training on assessing reproductive intentions have been called for in other studies in Zika-affected areas (Ali, Miller, & Gomez Ponce de Leon, 2017;Borges, Moreau, Burke, Dos Santos, & Chofakian, 2018;Shaw et al, 2017), but efforts also should prioritize strategies that more broadly situate a woman's own perspectives on achieving her reproductive goals and be mindful of new models that suggest methods for doing this (Aiken et al, 2016).…”
Section: Implications For Policy and Practicementioning
confidence: 99%